Caring to know a name: An examination of New York City student attitudes towards knowing a tree's name. Issue 3 (14th December 2021) - Wyner, Yael; Doherty, Jennifer H.
Societal Impact Statement: As the world becomes more urbanized, people place less value on knowing the biodiversity that surrounds them. Engagement with trees is hindered by an additional barrier, plant blindness, the tendency of people to ignore plants entirely. To help educators make tree diversity learning meaningful to students, this research aims to understand whether observing trees improves student dispositions towards knowing and observing trees, whether positive dispositions improve student learning about trees, and the reasons why urban middle school students care or do not care to know tree names. Summary: To improve student engagement with local plant diversity, we developed a curriculum for New York City (NYC) students (Grades 6–8, ages 11–14) to help them scientifically observe the trees they pass daily. This study reports results from preassessments/postassessments that explore students' dispositions towards knowing and observing trees and how these dispositions relate to learning. Participants included 150 intervention and 100 comparison students. In addition, 19 students were interviewed at three different time points. Findings indicate that a tree observation and identification curriculum positively influenced students' dispositions towards knowing and observing trees, but 6 months after implementation, student interest had returned near to where it had begun. In addition, socioeconomic status had little impact on students' dispositions, and no relationship was found between dispositions and learning. Findings also show that as a baseline, about 25% of students care about knowing a tree's name. We grouped the reasons students provided into 17 categories, 10 for caring and 7 for not caring. The most frequently stated categories for caring were liking to know, knowing a name helps me know more, and knowing a tree's name helps me know my surroundings. The most stated categories for not caring were that knowing a tree's name is unimportant for my day‐to‐day life and all trees look the same. Student reasons for caring and not caring are a compelling guide to the difficult task of making trees meaningful for students, an important step for empowering students to learn more about the trees that surround them. Abstract : As the world becomes more urbanized, people place less value on knowing the biodiversity that surrounds them. Engagement with trees is hindered by an additional barrier, plant blindness, the tendency of people to ignore plants entirely. To help educators make tree diversity learning meaningful to students, this research aims to understand whether observing trees improves student dispositions towards knowing and observing trees, whether positive dispositions improve student learning about trees, and the reasons why urban middle school students care or do not care to know tree names.